Independent predictors of major cardiovascular events as quantitatively assessed by coronary CT-angiography: a long-term follow-up analysis. (14th October 2021) - Bittner, D; Roesner, C; Kilian, T; Goeller, M; Dey, D; Raaz-Schrauder, D; Achenbach, S; Marwan, M
Abstract: Introduction: Quantitative CT coronary angiography using semi-automated software provides detailed information about plaque volume and high-risk plaque characteristics, beyond traditional measures like diameter stenosis. We assessed the potential value of plaque quantity and morphology to independently predict MACE in a cohort with long-term follow up. Methods: In this secondary analysis of 301 symptomatic patients undergoing coronary CTA at baseline, total plaque volume (TPV), non-calcified- (NCPV), calcified- (CPV) and vulnerable coronary plaque volume (in mm 3 ), diameter stenosis (in %) and remodeling index were quantified using semi-automated software (Autoplaque version 2.5, Cedars-Sinai Medical Center, Los Angeles, CA). Patients were followed for major cardiovascular events (MACE), defined as a composite of cardiovascular death, myocardial infarction and coronary revascularization. Optimal thresholds for each quantitative CTA measure were computed using CART-algorithm (Classification and Regression Trees). Results: Complete follow-up was available for 234 (78%) patients. The mean age was 59±10 years. Over a median follow-up of 10.7 years, the composite outcome occurred in 34 (15%) patients (5 patients with cardiovascular death, 6 with myocardial infarction, 26 with revascularization). Patients experiencing MACE had more frequently hypertension (p=0.03) and a higher Framingham risk score (p=0.002). Survival anaylsis using cox proportional hazard ratios showed significant univariate associations between MACE and TPV (HR 5.16; 95% CI 1.58–16.89; p=0.007), NCPV (HR 4.83; 95% CI 1.45–15.81; p=0.009), CPV (HR 2.86; 95% CI 1.39–5.86; p=0.004), vulnerable plaque volume (HR 3.35; 95% CI 1.52–7.41; p=0.003), diameter stenosis (HR 5.19; 95% CI 2.64–10.22; p<0.001) and remodeling index (HR 4.24; 95% CI 2.03–8.86; p<0.001). In multivariable cox regression analysis diameter stenosis (HR 3.70; 95% CI 1.72–7.93; p=0.001) and remodeling index (HR 2.69; 95% CI 1.19–6.09; p=0.018) remained significant independent predictors of MACE, adjusted for Framingham risk score (HR 2.56; 95% CI 1.26–5.22; p=0.010), however plaque volume and plaque subcomponents did not. Conclusion: On long term follow-up, remodeling index and coronary diameter stenosis obtained by quantitative coronary CT angiography independently predicted MACE on multivariable assessment. More comprehensive plaque assessment algorithms including plaque volume as well as plaque subcomponents were significantly associated with MACE in univariate, but not multivariate analysis after adjustment for diameter stenosis and remodeling index. Funding Acknowledgement: Type of funding sources: None.